Edukasi Hospitality dan Pariwisata Berkelanjutan : Pembinaan Kepada Mahasiswa UNNES dalam Menghadapi Pergaulan Modern - Ahmad Mansur (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
This community service program aims to address the problem of UNNES students' involvement in clubbing and promiscuity activities through a hospitality and sustainable tourism education approach. The activity was carried out on January 24, 2025 at Jogan Gumelar Borobudur involving 47 of the target 50 students in semesters 2 and 4. The program implementation methods include service excellence training, sharing tourism industry experiences, personal branding workshops, and ongoing mentoring. The results of the program showed an increase in participants' understanding by 30.2% (from an average pre-test score of 65.5 to a post-test of 85.3) regarding industry standards and hospitality ethics. As many as 89% of participants committed to avoiding clubbing and 92% understood the importance of professional ethics in the tourism industry. The participation rate reached 94% with a composition of 65% women and 35% men. This program contributes to forming quality and integrated tourism human resources through the integration of hospitality values with student character building. The obstacles faced included 15% of participants being late, unstable internet connection, and limited discussion time, but these could be overcome through the implementation of a strict attendance system, committee hotspot backup, and the addition of online discussion sessions.